La Maison de la Vierge à Éphèse. - Manoël Pénicaud (European Journal of Turkish Studies)
This article will trace from a diachronic perspective the different steps towards the construction and heritagisation of the House of Mary [Meryem Ana Evi], the presumed location of her Assumption, discovered in the late XIXth century near Ephesus. Within a few years, it had become a local center of pilgrimage, promoted by French Catholic missionaries from Izmir, and later recognized as a holy place by Rome. Despite its extinction due to the First World War and the establishment of the Kemalist Republic, a particular focus will be on the period in the 1950s when the site was nationalized by the Turkish state. While its Christian heritage has often been discredited, the House of the Virgin has precociously benefited from the protective and international aura of the antique city of Ephesus -one of the jewels of Turkish archaeological heritage- to find a second life.Nowadays, the shrine is visited each year by hundreds of thousands of visitors (pilgrims and / or tourists, Christians and Muslims) from around the world, making it an economic centre of religious heritage in Turkey. This article will show how the State has appropriated a shrine to develop -very pragmatically- a language of tolerance and multi-confessional opening, which however, contrasts with opposed cultural policies and values primarily Turkish-Sunni identity. Thus, Mary’s House is a special case of manufacture and treatment of the Christian heritage in Turkey.